Organ-Specific Immune-Related Adverse Events for PD-1 Antibodies in Lung Cancer Treatment - Zheng, Xiaohu; Wei, Haiming (Frontiers in Oncology, 2021)
Anti-PD-1 therapy has revolutionized the clinical treatment of lung cancer. With the increasing number of lung cancer patients being treated, there is also an increase in the number of immune-related adverse events (irAEs) being reported. These irAEs involve multiple organs and systems, mainly manifest as inflammatory side effects, and are different from the adverse events observed with traditional lung cancer treatment. These effects are often mild and treatable and reversible; however, in a few cases the side effects can be severe and lead to termination of immunotherapy. Management involves glucocorticoid-based related immunomodulators, which should be carefully prescribed to balance the efficacy and side effects of the PD-1 antibody treatment. This review will describe the characteristics and mechanisms of irAEs in specific organs, and will serve as a guide to help optimize treatment plans and improve patient outcomes.